Environment-friendly automotive carpet and preparation method thereof

Through the multi-layer structure automotive carpet design, including gradient density POE sound insulation layer and modified sulfates, the existing automotive carpet materials have solved the odor, interface compatibility and sound insulation problems, achieving higher environmental protection, comfort and durability.

CN120171147AActive Publication Date: 2025-06-20YANTAI ZHENGHAI HIGH TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510662759.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-06-20
Estimated Expiration
2045-05-22

AI Technical Summary

Technical Problem

Existing automotive carpet materials such as PVC and TPO have problems with odor, incompatibility of interfaces, insufficient sound insulation and flexibility during processing and use, making it difficult to meet the high requirements of environmental protection, comfort and durability.

Method used

The automotive carpet design adopts a multi-layer structure, including the TPO skin layer, the PU foam layer and the waterproof membrane layer. The TPO skin layer consists of the TPO surface layer and the POE sound insulation layer. The POE sound insulation layer adopts a gradient density design that increases from top to bottom density, and uses modified sulfate and aminosilane coupling agent to improve interface binding and sound insulation performance.

Benefits of technology

It significantly reduces the release of harmful odors, improves the flexibility and sound insulation performance of the carpet, extends the service life of the product, and meets the high requirements of environmental protection, comfort and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of automotive carpets, and particularly discloses an environment-friendly automotive carpet and a preparation method thereof. The environment-friendly automobile carpet sequentially comprises a TPO surface layer, a PU foam layer and a waterproof film layer from top to bottom, the TPO surface layer sequentially comprises a TPO surface layer and a POE sound insulation layer from top to bottom; the thickness of the TPO surface layer ranges from 1.5 mm to 2.8 mm, and the thickness of the TPO surface layer ranges from 0.5 mm to 1 mm. The environment-friendly automobile carpet has the characteristics of low odor and high sound insulation, meets the requirements of environmental protection, and has excellent flexibility and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automotive carpets, and more specifically, it relates to an environmentally friendly automotive carpet and a preparation method thereof. Background Art

[0002] With the booming development of the global automotive industry, consumers' requirements for the environmental protection, comfort, and durability of automotive interiors are increasing day by day. As an important decorative and functional component inside the vehicle, automotive carpets not only affect the comfort and aesthetics of the vehicle but also are directly related to the air quality inside the vehicle and the driving experience, and need to meet increasingly strict environmental protection standards and health and safety requirements.

[0003] Currently, polyvinyl chloride (PVC) is commonly used as the skin material in the manufacture of carpets for trucks, taxis, and minibuses. PVC has dominated in the past few decades due to its excellent waterproof, wear-resistant, and cost advantages. However, its environmental performance is poor, and it is easy to release harmful gases such as hydrogen chloride and dioxins at high temperatures, resulting in a decrease in the air quality inside the vehicle. Long-term exposure will endanger the health of the driver and passengers. Moreover, it has high low-temperature brittleness, high hardness, and a rigid touch. Traditional PVC automotive carpets also have insufficient aging resistance, and are prone to deformation, cracking, and fading after long-term use, making it difficult to meet the high requirements of current automotive interior materials for environmental protection, comfort, and durability.

[0004] Due to its excellent environmental performance, weather resistance, and processing performance, thermoplastic polyolefin (TPO) materials have gradually become a popular material to replace PVC. In view of the above related technologies, the present application finds that there are still problems with a relatively large odor in automotive carpets prepared by replacing PVC with TPO, and there are also problems such as insufficient interfacial compatibility between the TPO skin and other layers, insufficient sound insulation and flexibility, easy delamination between layers, which affects the overall performance of the product and insufficient durability. How to apply TPO materials to the manufacture of automotive carpets and give full play to and maintain their performance advantages is still a research difficulty in the current technical field. Summary of the Invention

[0005] In order to reduce the odor of automotive carpets, improve the flexibility and sound insulation performance of automotive carpets, and meet the multiple requirements of current automotive interior materials for green environmental protection, comfort, and sound insulation, the present application provides an environmentally friendly automotive carpet and a preparation method thereof.

[0006] In a first aspect, the present application provides an environmentally friendly automotive carpet, adopting the following technical solution: An environmentally friendly automotive carpet successively includes a TPO skin layer, a PU foam layer, and a waterproof film layer from top to bottom; The TPO skin layer successively includes a TPO surface layer and a POE sound insulation layer from top to bottom; The POE sound insulation layer successively includes a light surface layer, an intermediate layer, and a heavy bottom layer from top to bottom.

[0007] By adopting the above technical solutions, all the TPO, POE, and PU materials used in this application are environmentally friendly materials with high thermal stability. Compared with traditional PVC or automotive interior carpets containing PVC materials, the prepared multi-layer automotive carpet significantly reduces the VOCs generated during processing and use and the release of harmful substances at high temperatures, ensuring the air quality inside the vehicle during use.

[0008] The TPO skin layer is divided into two layers: the TPO surface layer and the POE sound insulation layer, achieving a combination of hardness and softness, effectively improving the flexibility of the overall material, reducing stress concentration, and delaying the propagation of cracks.

[0009] Furthermore, the POE sound insulation layer successively includes a lightweight surface layer, a middle layer, and a heavy bottom layer from top to bottom, with the density increasing from top to bottom. On the one hand, it forms an interface with a gradually changing hardness, buffering the stress, and being able to reduce the risk of delamination caused by stress concentration due to the hardness difference between TPO and POE. The POE lightweight surface layer is softer and has better compatibility with the TPO surface layer during the thermoforming process, thus enhancing the interfacial bonding force between the TPO surface layer and the POE sound insulation layer.

[0010] On the other hand, the density of the POE sound insulation layer increases successively from top to bottom. This design of the gradient density level optimizes the sound insulation performance of the entire frequency band through the anti-gradient of the acoustic impedance. The heavy bottom layer can effectively block the transmission of low-frequency sound waves and effectively isolate the body sheet metal sound. The middle layer serves as a transition, achieving a continuous change in the acoustic impedance, suppressing mid-frequency resonance, reducing sound transmission, and the lightweight surface layer can reduce the reflection of high-frequency sound waves, matching the air acoustic impedance and enhancing the overall sound absorption coefficient of the POE sound insulation layer.

[0011] In addition, the density of the PU foam layer in this application is relatively low, about 60 - 70 kg / m 3 , and the composite of the heavy bottom layer and the PU foam layer can provide rigid support for the PU foam layer without losing elasticity, enhancing the ability of the PU foam layer to resist load deformation, thereby enhancing the overall durability of the environmentally friendly carpet.

[0012] Optionally, the raw materials of the lightweight surface layer, the middle layer, and the heavy bottom layer of the POE sound insulation layer all include POE particles, POE-g-MAH, and modified sulfate. The modified sulfate is a blend of barium sulfate and calcium sulfate with a mass ratio of (2 - 7):1 after surface modification by an amino silane coupling agent.

[0013] Optionally, the modified sulfate in the light surface layer is a blend of barium sulfate and calcium sulfate with a mass ratio of 2:1 after surface modification with an amino-silane coupling agent; the modified sulfate in the intermediate layer is a blend of barium sulfate and calcium sulfate with a mass ratio of 5:1 after surface modification with an amino-silane coupling agent; the modified sulfate in the heavy bottom layer is a blend of barium sulfate and calcium sulfate with a mass ratio of 7:1 after surface modification with an amino-silane coupling agent.

[0014] This application discovers that the combination of the characteristics of calcium sulfate's light porous structure for absorbing high-frequency sound waves and barium sulfate's high density for blocking low-frequency sound waves enables the regulation of gradient density by adjusting the mixing ratio of calcium sulfate and barium sulfate, achieving sound insulation across the entire frequency band at low cost. As inorganic sound insulation fillers, calcium sulfate and barium sulfate form a modified sulfate with stable properties, which can form a physical barrier in the organic matrix, reducing the direct contact between polymer molecular chains, thereby reducing the occurrence of thermal decomposition reactions and further reducing the release of volatile organic compounds that may be generated during processing and use, and reducing odors.

[0015] Furthermore, in this application, the modified sulfate is obtained by surface-modifying calcium sulfate and barium sulfate with an amino-silane coupling agent, forming an organic-silane chain-inorganic crosslinked structure at the interface between calcium sulfate, barium sulfate, and POE. This significantly improves the dispersion of calcium sulfate and barium sulfate fillers in the POE matrix, enhances the interfacial bonding force between the inorganic filler and the organic matrix, and inhibits sound wave transmission.

[0016] In addition, the amino group introduced on the surface of the modified sulfate obtained by modifying with an amino-silane coupling agent can bind to the isocyanate groups in the PU foam layer, significantly enhancing the peel strength between the POE sound insulation layer and the PU foam layer under the action of strong chemical bond binding.

[0017] By adopting the above technical solution, the synchronous and collaborative optimization of acoustics and mechanics is achieved.

[0018] Optionally, the density of the light surface layer is (0.9 ± 0.05) g / cm³, the density of the intermediate layer is (1.5 ± 0.05) g / cm³, and the density of the heavy bottom layer is (1.8 ± 0.05) g / cm³.

[0019] Optionally, calculated by weight, the raw materials of the TPO surface layer include 50 - 60 parts of TPO particles, 20 - 30 parts of PP-g-MAH, 7 - 12 parts of adsorption filler, 1 - 2 parts of additive, and 1 - 10 parts of pigment. The additive is a hindered amine light stabilizer, and the pigment is carbon black.

[0020] Optionally, the additive is a hindered amine light stabilizer.

[0021] Optionally, the adsorption filler is a composition of hollow glass microspheres and nano-clay with a mass ratio of 1:(1-2).

[0022] By adopting the above technical solution, the addition of the inorganic adsorption filler can not only adsorb odor molecules, but also enhance the wear resistance and aging resistance of the TPO skin layer. Both the fine pore silica gel and the hollow glass microspheres have porous structures, which can effectively capture the volatile VOCs generated during the TPO processing. The nano-clay has a lamellar structure and a high specific surface area, and can capture small molecule volatiles through an intercalation structure, further reducing the release of harmful substances from the environmental protection carpet in different temperature environments and ensuring the air quality in the vehicle.

[0023] Optionally, the thickness of the TPO skin layer is 1.5-2.8 mm, and the thickness of the TPO surface layer is 0.5-1 mm.

[0024] By adopting the above technical solution, the reasonable thickness setting can ensure that the sound wave has enough propagation path to be absorbed in the gradient layer, and at the same time avoid the increase in rigidity caused by the excessive thickness of the material, taking into account both wear resistance and flexibility.

[0025] Optionally, the waterproof membrane is a TPU waterproof membrane.

[0026] Optionally, the thickness of the waterproof membrane is (0.6±0.05) mm.

[0027] By adopting the above technical solution, using the waterproof membrane can not only replace the release agent in the PU foaming to improve the working environment, but also increase the sealing performance of the environmental protection carpet, prevent the carpet from absorbing moisture during use, and protect the vehicle bottom sheet metal from rusting due to moisture.

[0028] In the second aspect, the present application provides a preparation method of an environmental protection automotive carpet, adopting the following technical solution: A preparation method of an environmental protection automotive carpet includes the following steps: S1: According to the raw material ratio, perform melt co-extrusion compounding through a multi-layer co-extrusion device to form a TPO skin layer composed of a TPO surface layer and a POE sound insulation layer from top to bottom, and then perform thermoforming to form a preliminary automotive carpet; S2: Place the preliminary automotive carpet in the lower mold of the foaming mold, place the waterproof membrane in the upper mold of the foaming mold, pour the PU foaming material along a preset track to prepare a PU foaming layer, and after pouring, close the mold, keep pressure and cure to obtain a prefabricated automotive carpet; S3: Place the prefabricated automotive carpet on the water cutting template, after vacuum adsorption positioning, the water cutting robot cuts off the excess side holes along the preset track to obtain the finished product.

[0029] By adopting the above technical solutions, this application uses environmentally friendly materials and green production processes, effectively reducing the release of harmful substances during processing, precisely controlling the thickness and density of each layer, and having a strong interfacial bond between layers, ensuring the synchronous and collaborative optimization of the acoustic and mechanical properties of the environmentally friendly carpet. The finished product has excellent flexibility and aging resistance, effectively reducing the problems of cracking and deformation that are prone to occur during long-term use.

[0030] Optionally, the PU foam material includes polyether polyol and isocyanate with a mass ratio of (1.6 - 1.8):1.

[0031] Optionally, the conditions for thermoforming in step S1 are: heating furnace temperature 370 ± 10 °C, heating time 90 ± 10 s, adsorption time 50 ± 5 s, vacuum adsorption negative pressure ≤ -0.02 MPa, and mold temperature ≤ 40 °C.

[0032] In summary, this application has the following beneficial effects: 1. This application uses environmentally friendly materials and processes, effectively reducing the release of harmful odors during the processing of automotive carpets and their use in different temperature environments, ensuring the air quality inside the vehicle. The TPO skin layer is prepared by laminating the TPO surface layer with the POE sound insulation layer having a gradient density structure, forming an interface with a gradual change from hard to soft, effectively buffering stress, achieving a combination of hard and soft, effectively improving the flexibility of the TPO skin layer, and reducing the risk of delamination caused by stress concentration due to the hardness difference between the TPO layer and the POE layer.

[0033] 2. The POE sound insulation layer of this application adopts a density gradient with increasing density from top to bottom. The heavy bottom layer and the light top layer can effectively block the transmission of low-frequency and high-frequency sound waves respectively, and the intermediate layer is used for transition to achieve a continuous change in acoustic impedance. By optimizing the anti-gradient of acoustic resistance, the sound insulation performance in the full frequency range is optimized, enabling the environmentally friendly carpet to effectively block the body sheet metal sound and tire and road noise, reducing the echo inside the vehicle, and significantly improving the overall sound insulation and sound absorption effect.

[0034] 3. For the POE sound insulation layer of this application, the design of gradient density is achieved by regulating the ratio and dosage of calcium sulfate and barium sulfate. The modified sulfate is obtained by mixing and modifying calcium sulfate and barium sulfate with an amino silane coupling agent, which not only enhances the dispersion uniformity of inorganic fillers in the POE matrix but also effectively enhances the interfacial bonding force between the TPO surface layer and the POE sound insulation layer, and between the POE sound insulation layer and the PU foam layer through the action of the coupling agent, realizing the synchronous and collaborative optimization of acoustics and mechanics, meeting the requirements of green environmental protection. Specific Embodiments

[0035] The following embodiments further illustrate this application in detail. Raw Materials

[0036] Unless otherwise specified, the raw materials used in the preparation examples, examples and comparative examples in this application are all commercially available products, specifically: POE particles, selected from Mitsui Chemicals, DF610; POE-g-MAH, selected from Dow Chemical, N216; TPO particles, selected from Teknor Apex, TL 2468A; PP-g-MAH, selected from Exxon, PO1015; Hollow glass microspheres with a particle size of 10 - 20 μm; Nanoclay with a diameter of 20 - 30 μm; Hindered amine light stabilizer, selected from Beijing Tian Gang Additives, light stabilizer 622; Carbon black, CAS: 1333 - 86 - 4; Polyether polyol, a fast-curing all-water foaming polyether blend, selected from Wanhua Chemical, WANEFLEXTM 542T; Isocyanate, a mixture of polyol-modified diphenylmethane diisocyanate and polymethylene polyphenyl isocyanate, selected from Wanhua Chemical, WANNATE® 8018. Preparation example of modified sulfate

[0037] Preparation example 1 Modified sulfate, the raw materials include barium sulfate and calcium sulfate with a mass ratio of 2:1, and its preparation method includes the following steps: Add the silane coupling agent to ethanol, stir evenly to prepare a 5% coupling agent solution, add the mixture of calcium sulfate and barium sulfate to the coupling agent solution, carry out ultrasonic stirring reaction at 40 °C for 5 h, then centrifuge, wash and vacuum dry at 80 °C to obtain the modified sulfate, where the silane coupling agent is amino silane coupling agent KH-550.

[0038] Preparation example 2 Modified sulfate, different from preparation example 1 in that the raw materials include barium sulfate and calcium sulfate with a mass ratio of 5:1, and the other steps are the same as those in preparation example 1.

[0039] Preparation example 3 Modified sulfate, different from preparation example 1 in that the raw materials include barium sulfate and calcium sulfate with a mass ratio of 7:1, and the other steps are the same as those in preparation example 1.

[0040] Preparation example 4 Modified sulfate, different from preparation example 1 in that the calcium sulfate in the raw materials is replaced with an equal mass of hollow glass microspheres, and the other steps are the same as those in preparation example 1.

[0041] Preparation example 5 Modified sulfate, different from Preparation Example 2 in that calcium sulfate in the raw materials is replaced with hollow glass microspheres of equal mass, and other steps are the same as those in Preparation Example 2.

[0042] Preparation Example 6 Modified sulfate, different from Preparation Example 3 in that calcium sulfate in the raw materials is replaced with hollow glass microspheres of equal mass, and other steps are the same as those in Preparation Example 3. Example Example 1

[0043] An environment-friendly automotive carpet, which sequentially includes a TPO skin layer, a PU foam layer and a waterproof film layer from top to bottom. The TPO skin layer sequentially includes a TPO surface layer and a POE sound insulation layer from top to bottom. The POE sound insulation layer sequentially includes a light surface layer, a middle layer and a heavy bottom layer from top to bottom. The waterproof film is a TPU waterproof film. The raw materials and dosages of each layer of the TPO surface layer are shown in Table 1, wherein the adsorption filler is a pretreated adsorption filler, including hollow glass microspheres and nano-clay with a mass ratio of 1:1.5, the auxiliary agent is a hindered amine light stabilizer, the pigment is carbon black. The raw materials and dosages of each layer of the POE sound insulation layer are shown in Table 2, wherein the modified sulfate of the light surface layer is obtained from Preparation Example 1, the modified sulfate of the middle layer is obtained from Preparation Example 2, and the modified sulfate of the heavy bottom layer is obtained from Preparation Example 3.

[0044] Table 1

[0045] Table 2

[0046] The preparation method of the above environment-friendly automotive carpet includes the following steps: S1: Mix hollow glass microspheres and nano-clay and then conduct the following pretreatment: Add a silane coupling agent to ethanol, stir evenly to prepare a 5% coupling agent solution, add the mixed hollow glass microspheres and nano-clay to the coupling agent solution, conduct ultrasonic stirring reaction at 30°C for 2 h, then centrifuge, wash and vacuum dry at 80°C to obtain the pretreated adsorption filler, wherein the silane coupling agent is an amino silane coupling agent KH-550; S2: Prepare raw materials according to the raw material ratios of the TPO surface layer and the POE sound insulation layer and then mix them. Through a multi-layer co-extrusion device, feed materials into different barrels respectively and then conduct melt co-extrusion compounding to form a TPO skin layer that is sequentially the TPO surface layer, the POE light surface layer, the middle layer and the heavy bottom layer from top to bottom, and then conduct thermoforming. The temperature of the heating furnace is 370±10°C, the heating time is 90±10 s, the adsorption time is 50±5 s, the vacuum adsorption negative pressure ≤ -0.02 MPa, and the mold temperature ≤ 40°C to form a preliminary automotive carpet; Among them, the thickness of the TPO surface layer is 0.8 mm; The density of the light surface layer is (0.9 ± 0.05) g / cm³, and the thickness is 0.3 mm; The density of the middle layer is (1.5 ± 0.05) g / cm³, and the thickness is 0.4 mm; The density of the heavy bottom layer is (1.8 ± 0.05) g / cm³, and the thickness is 0.5 mm; The total thickness of the TPO skin layer is 2 mm; S3: Place the initial form of the automotive carpet in the lower mold of the foaming mold, place the TPU waterproof film in the upper mold of the foaming mold, pour the PU foaming material along the preset trajectory to prepare the PU foaming layer. After pouring, close the mold and perform pressure holding and curing to obtain the prefabricated automotive carpet. The density of the PU foaming layer is (0.065 ± 0.005) g / cm 3 , and the PU foaming material includes polyether polyol and isocyanate with a mass ratio of 1.6:1; S4: Place the prefabricated automotive carpet on the water cutting template. After vacuum adsorption positioning, the water cutting robot cuts off the excess side holes along the preset trajectory to obtain the product. Among them, the air source pressure is 0.5 ± 0.05 MPa, the pressure of the high-pressure water generator is 3200 ± 200 bar, and the vacuum adsorption negative pressure ≤ -1.0 Kpa.

[0047] Example 2 An environment-friendly automotive carpet, which is different from Example 1 in that the raw materials and dosages of each layer of the TPO surface layer are shown in Table 1, where the adsorption filler is a pretreated adsorption filler, including hollow glass microspheres and nano-clay with a mass ratio of 1:2, and the raw materials and dosages of each layer of the POE sound insulation layer are shown in Table 2; Among them, the thickness of the TPO surface layer is 0.7 mm, The density of the light surface layer is (0.9 ± 0.05) g / cm³, and the thickness is 0.4 mm; The density of the middle layer is (1.5 ± 0.05) g / cm³, and the thickness is 0.5 mm; The density of the heavy bottom layer is (1.8 ± 0.05) g / cm³, and the thickness is 0.7 mm; The total thickness of the TPO skin layer is 2.3 mm; The density of the PU foaming layer is (0.065 ± 0.005) g / cm 3 , and the PU foaming material includes polyether polyol and isocyanate with a mass ratio of 1.8:1; All other steps are the same as those in Example 1.

[0048] Example 3 An environmentally friendly automotive carpet, which is different from that of Example 1 in that the raw materials and dosages of each layer of the TPO surface layer are shown in Table 1, wherein the adsorption filler is a pretreated adsorption filler, including hollow glass microspheres and nano-clay with a mass ratio of 1:1, and the raw materials and dosages of each layer of the POE sound insulation layer are shown in Table 2; wherein the thickness of the TPO surface layer is 0.5 mm, the density of the light surface layer is (0.9 ± 0.05) g / cm³, and the thickness is 0.2 mm; the density of the intermediate layer is (1.5 ± 0.05) g / cm³, and the thickness is 0.3 mm; the density of the heavy bottom layer is (1.8 ± 0.05) g / cm³, and the thickness is 0.5 mm; the total thickness of the TPO skin layer is 1.5 mm; the density of the PU foam layer is (0.065 ± 0.005) g / cm 3 , and the PU foam material includes polyether polyol and isocyanate with a mass ratio of 1.7:1; All other steps are the same as those in Example 1.

[0049] Example 4 An environmentally friendly automotive carpet, which is different from that of Example 1 in that the raw materials and dosages of each layer of the TPO surface layer are shown in Table 1, and the raw materials and dosages of each layer of the POE sound insulation layer are shown in Table 2; wherein the thickness of the TPO surface layer is 1 mm, the density of the light surface layer is (0.9 ± 0.05) g / cm³, and the thickness is 0.4 mm; the density of the intermediate layer is (1.5 ± 0.05) g / cm³, and the thickness is 0.6 mm; the density of the heavy bottom layer is (1.8 ± 0.05) g / cm³, and the thickness is 0.8 mm; the total thickness of the TPO skin layer is 2.8 mm; the density of the PU foam layer is (0.065 ± 0.005) g / cm 3 , and the PU foam material includes polyether polyol and isocyanate with a mass ratio of 1.8:1; All other steps are the same as those in Example 1.

[0050] Example 5 An environmentally friendly automotive carpet, which is different from that of Example 1 in that the modified sulfate in the light surface layer of the POE sound insulation layer is obtained from Preparation Example 4, the modified sulfate in the intermediate layer is obtained from Preparation Example 5, and the modified sulfate in the heavy bottom layer is obtained from Preparation Example 6. All other steps are the same as those in Example 1.

[0051] Example 6 An environmentally friendly automotive carpet, which is different from Example 1 in that calcium sulfate and barium sulfate are not surface-modified with an amino silane coupling agent, and other steps are the same as those in Example 1.

[0052] Example 7 An environmentally friendly automotive carpet, which is different from Example 1 in that nano-clay is not added, and the adsorption filler is only the hollow glass microspheres obtained after pretreatment, and other steps are the same as those in Example 1.

[0053] Example 8 An environmentally friendly automotive carpet, which is different from Example 1 in that hollow glass microspheres are not added, and the adsorption filler is only the nano-clay obtained after pretreatment, and other steps are the same as those in Example 1.

[0054] Example 9 An environmentally friendly automotive carpet, which is different from Example 1 in that the adsorption filler is not added, and the adsorption filler in the raw materials is replaced with TPO particles of equal mass, and other steps are the same as those in Example 1. Comparative Example

[0055] Comparative Example 1 An environmentally friendly automotive carpet, which is different from Example 1 in that the intermediate layer and the heavy bottom layer are not provided in the TPO skin layer. The TPO skin layer includes a TPO surface layer and a POE sound insulation layer from top to bottom. The thickness of the TPO surface layer is 0.8 mm, the density of the POE sound insulation layer is (0.9 ± 0.05) g / cm³, the thickness is 1.2 mm, and the total thickness of the TPO skin layer is 2 mm. Other steps are the same as those in Example 1.

[0056] Comparative Example 2 An environmentally friendly automotive carpet, which is different from Example 1 in that the light surface layer and the heavy bottom layer are not provided in the TPO skin layer. The TPO skin layer includes a TPO surface layer and a POE sound insulation layer from top to bottom. The thickness of the TPO surface layer is 0.8 mm, the density of the POE sound insulation layer is (1.5 ± 0.05) g / cm³, the thickness is 1.2 mm, and the total thickness of the TPO skin layer is 2 mm. Other steps are the same as those in Example 1.

[0057] Comparative Example 3 An environmentally friendly automotive carpet, which is different from Example 1 in that the light surface layer and the intermediate layer are not provided in the TPO skin layer. The TPO skin layer includes a TPO surface layer and a POE sound insulation layer from top to bottom. The thickness of the TPO surface layer is 0.8 mm, the density of the POE sound insulation layer is (1.8 ± 0.05) g / cm³, the thickness is 1.2 mm, and the total thickness of the TPO skin layer is 2 mm. Other steps are the same as those in Example 1.

[0058] Comparative Example 4 An environment-friendly automotive carpet, which is different from that of Example 1 in that the TPO skin layer sequentially includes a TPO surface layer and a POE sound insulation layer from top to bottom. The POE sound insulation layer sequentially includes a heavy surface layer, an intermediate layer, and a light bottom layer from top to bottom, wherein the thickness of the TPO surface layer is 0.8 mm; The density of the heavy surface layer is (1.8 ± 0.05) g / cm³, and the thickness is 0.5 mm; The density of the intermediate layer is (1.5 ± 0.05) g / cm³, and the thickness is 0.4 mm; The density of the light bottom layer is (0.9 ± 0.05) g / cm³, and the thickness is 0.3 mm; The total thickness of the TPO skin layer is 2 mm; All other steps are the same as those in Example 1.

[0059] Performance detection test The following relevant performance detection tests are carried out on an environment-friendly automotive carpet obtained in Examples 1-9 and Comparative Examples 1-4.

[0060] 1. Odor level detection: The odor test is carried out with reference to the relevant test methods specified in PV3900 of Volkswagen Group. An environment-friendly automotive carpet obtained in Examples 1-9 and Comparative Examples 1-4 is respectively cut into a test sample of (50 ± 5) cm³ for standard cutting, and each group of test samples is respectively placed in a 1L odor bottle, heated at (80 ± 2) °C for 2 h, and then cooled to (65 ± 2) °C. Three professional odor assessment personnel detect the odor of each group of test samples, and the detection standards are as follows: Level 1: No sensory odor; Level 2: Slight odor, detectable but non-irritating, and will not cause discomfort; Level 3: Obvious odor, non-irritating, and will not cause discomfort; Level 4: Stronger odor, with an irritating odor, unacceptable; Level 5: Strong odor, obviously irritating, seriously unacceptable; Level 6: Strongly irritating or harmful odor, intolerable; After rating by three professional odor assessment personnel, the average value is taken as the odor detection result of each group of environment-friendly automotive carpets and recorded in Table 3; 2. Hardness: The Shore A hardness of the TPO skin layer (i.e., the initial form of the automotive carpet) is detected with reference to the relevant provisions of GB / T 531.1. Each group of tests is carried out 3 times, and the average value of the 3 test results is taken as the final result and recorded in Table 3; 3. Dyn value: Use dyn pens of different models to draw a line on the side of the POE sound insulation layer in contact with the PU foam layer. Observe whether it shrinks and condenses into liquid beads within 2 - 3 s. If it forms a continuous straight line without immediate shrinkage, it indicates that the surface tension of the material has reached the tension value of the pen. If it is intermittent where the pen tip touches and condenses into small liquid beads, it indicates that the tension value of the test pen has not been reached; 4. Abrasion resistance: Detect the abrasion resistance according to the relevant regulations of Q / ZZ 11599 - 2020, calculate the weight loss, and require that the mass change ≤ 100 mg, and the PU foam layer is not exposed. Each group of tests is carried out 3 times, and the average value of the 3 test results is taken as the final result and recorded in Table 3; 5. Acoustic performance: Refer to the relevant regulations of GB / T 18696.2 to detect the average sound absorption coefficient in different frequency bands (250 - 500 Hz, 500 - 2000 Hz, and 2000 - 5000 Hz). Each group of tests is carried out 3 times, and the average value of the 3 test results is taken as the final result and recorded in Table 3.

[0061] Table 3

[0062] From the performance test results of Examples 1 - 9 in Table 3, it can be seen that the odor detection grade of an environmentally friendly automotive carpet of this application after high - temperature treatment is 3 - 4. This indicates that the automotive carpet of this application can maintain good environmental protection under processing and temperature conditions in different seasons, and will not release harmful substances due to high - temperature use, affecting the air quality inside the vehicle; from the test results of its hardness value, abrasion resistance, sound insulation and sound absorption performance, it can be seen that the automotive carpet of this application has excellent flexibility and a balance with rigidity, is durable, can achieve full - frequency sound absorption and sound insulation performance, and can effectively isolate the noises generated during vehicle use, such as engine noise, vehicle bottom sheet metal sound, in - vehicle audio noise, wind noise, and braking sound; in addition, the dyn value between the TPO skin layer and the PU foam layer of the environmentally friendly automotive carpet of this application is ≥ 40, which indicates that the TPO surface layer and the PU foam layer can be stably bonded, with a high peel strength, and can effectively prevent separation between different layers.

[0063] From the performance test results of Examples 1 - 4 and Examples 5 - 6, it can be seen that in Example 5, calcium sulfate is replaced by hollow glass microspheres, resulting in a decrease in the dyn value between the TPO skin layer and the PU foam layer, leading to a decrease in the interfacial bonding force between the TPO skin layer and the PU foam layer. This is because compared with other inorganic light fillers, the compatibility between barium sulfate and calcium sulfate is better, and the formed modified sulfate can exist more stably in the POE layer.

[0064] In Example 6, calcium sulfate and barium sulfate were not surface-modified. The dyne value between the TPO skin layer and the PU foam layer decreased significantly, resulting in a significant decrease in the interfacial bonding force between the TPO skin layer and the PU foam layer. This would cause delamination and peeling between the TPO skin layer and the PU foam layer due to insufficient interfacial bonding force, and it also affected the sound insulation effect of the POE sound insulation layer.

[0065] From the performance test results of Example 1 and Comparative Examples 1-4, it can be seen that when the POE sound insulation layer adopts a density gradient with increasing density from top to bottom, on the one hand, it can significantly enhance the full-frequency sound absorption and insulation performance of the automotive carpet, realizing continuous change of acoustic impedance. On the other hand, it can form an interface with a gradual change from hard to soft between the TPO surface layer, forming a stress buffer zone, effectively reducing the risk of delamination caused by stress concentration due to the hardness difference between TPO and POE, making the TPO skin layer softer and more flexible.

[0066] In Comparative Examples 1-3, only a POE sound insulation layer with a single density was used. Although it could achieve a certain isolation effect on external noise, it could not realize the full-frequency sound absorption and insulation effect. In particular, the hardness of the TPO skin layer formed by a single high-density POE sound insulation layer increased significantly, reducing the overall flexibility of the automotive carpet. In Comparative Example 4, a density gradient with decreasing density from top to bottom was used to prepare the POE sound insulation layer. This design was difficult to form an effective stress buffer zone between the TPO surface layer and the POE sound insulation layer, with a strong plastic feeling, and it was easy to cause delamination due to stress concentration caused by the hardness difference between the TPO surface layer and the POE sound insulation layer. The dyne value between the TPO skin layer and the PU foam layer also decreased, and this design significantly affected the sound absorption and insulation performance of the automotive carpet for high-frequency noise, reducing the isolation effect on noises such as in-car echoes and lowering the overall sound insulation effect of the automotive carpet.

[0067] From the performance test results of Example 1 and Examples 7-9, it can be seen that the addition of adsorption fillers can significantly reduce the odor level of the automotive carpet while improving wear resistance. In Examples 7-8, only a single hollow glass microsphere or a single nano-clay was used as the adsorption filler, compared with the mixture of the two, the odor level was higher and the wear resistance was also reduced. This may be because the spherical hollow glass microspheres and the lamellar nano-clay were compounded in the TPO skin layer to form a multi-level adsorption structure. The hollow structure of the hollow glass microspheres provided additional adsorption space, and the high specific surface area of the nano-clay further enhanced the adsorption ability.

[0068] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Those skilled in the art can make modifications without creative contributions to this embodiment according to needs after reading this specification, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. An environment-friendly automotive carpet, characterized in that, It successively includes a TPO skin layer, a PU foam layer, and a waterproof film layer from top to bottom; The TPO skin layer successively includes a TPO surface layer and a POE sound insulation layer from top to bottom; The POE sound insulation layer successively includes a light surface layer, a middle layer, and a heavy bottom layer from top to bottom.

2. The environment-friendly automotive carpet according to claim 1, characterized in that, The raw materials of the light surface layer, the middle layer, and the heavy bottom layer of the POE sound insulation layer all include POE particles, POE-g-MAH, and modified sulfate. The modified sulfate is a blend of barium sulfate and calcium sulfate with a mass ratio of (2-7):1 after surface modification by an amino silane coupling agent.

3. The environment-friendly automotive carpet according to claim 2, characterized in that, The density of the light surface layer is (0.9±0.05) g / cm³, the density of the middle layer is (1.5±0.05) g / cm³, and the density of the heavy bottom layer is (1.8±0.05) g / cm³.

4. The environment-friendly automotive carpet according to claim 1, characterized in that, By weight, the raw materials of the TPO surface layer include 50-60 parts of TPO particles, 20-30 parts of PP-g-MAH, 7-12 parts of adsorption filler, 1-2 parts of additive, and 1-10 parts of pigment. The additive is a hindered amine light stabilizer, and the pigment is carbon black.

5. The environment-friendly automotive carpet according to claim 4, characterized in that, The adsorption filler is a composition of hollow glass microspheres and nano-clay with a mass ratio of 1:(1-2).

6. The environment-friendly automotive carpet according to claim 1, characterized in that, The thickness of the TPO skin layer is 1.5-2.8 mm, and the thickness of the TPO surface layer is 0.5-1 mm.

7. The environment-friendly automotive carpet according to claim 1, characterized in that, The waterproof film is a TPU waterproof film.

8. A preparation method of the environment-friendly automotive carpet according to any one of claims 1-7, characterized in that, It includes the following steps: S1: According to the raw material ratio, through a multi-layer co-extrusion device for melt co-extrusion compounding, a TPO skin layer composed of a TPO surface layer and a POE sound insulation layer from top to bottom is formed, and then thermoforming is carried out to form a preliminary shape of the automotive carpet; S2: Place the preliminary shape of the automotive carpet in the lower mold of the foaming mold, place the waterproof film in the upper mold of the foaming mold, pour PU foaming material according to a preset trajectory to prepare a PU foam layer, and after pouring, close the mold, keep pressure and cure to obtain a prefabricated automotive carpet; S3: Place the prefabricated automotive carpet on the water cutting template, after vacuum adsorption positioning, the water cutting robot cuts off the excess side holes according to a preset trajectory to obtain the product.

9. The preparation method of the environment-friendly automotive carpet according to claim 8, characterized in that, The PU foaming material includes polyether polyol and isocyanate with a mass ratio of (1.6-1.8):

1.

10. The preparation method of the environment-friendly automotive carpet according to claim 8, characterized in that, The conditions for thermoforming in step S1 are: the temperature of the heating furnace is 370±10℃, the heating time is 90±10 s, the adsorption time is 50±5 s, the vacuum adsorption negative pressure ≤-0.02 MPa, and the mold temperature ≤40℃.

Citation Information

Patent Citations

  • Efficient sound insulation material and manufacturing method thereof

    CN103903608A

  • Filled thermoplastic polyolefin composition for use in vehicle sound-deadening applications

    CN104662081A

  • Carpet for commercial vehicle

    CN105966010A

  • Automobile carpet capable of enhancing sound insulation

    CN106080331A

  • Processing method of automotive carpet, automotive carpet and vehicle

    CN116038962A